2014
DOI: 10.1080/02188791.2014.934781
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ experience with inclusive education in Singapore

Abstract: Teachers' positive attitude is most critically and consistently associated with successful inclusion. However, little is known about teachers' first-hand encounters with inclusive education in Singapore. We present findings from a qualitative study on inclusion based on focus group interviews with 202 teachers from 41 resourced primary schools. The data were transcribed and coded using Interpretive Phenomenological Analysis and NVIVO software. Two broad clusters identified were teachers' positive and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 22 publications
1
17
0
4
Order By: Relevance
“…They are linked via behavioral intentions to behavior. Thus, it could be argued that attitudes toward inclusion are theoretically linked to teaching behavior that has been shown in empirical studies (e.g., Yeo et al, 2014). Therefore, more positive attitudes are considered to be the most influential factor for implementing successful inclusion (Avramidis and Norwich, 2002).…”
Section: Implicit and Explicit Attitudesmentioning
confidence: 99%
“…They are linked via behavioral intentions to behavior. Thus, it could be argued that attitudes toward inclusion are theoretically linked to teaching behavior that has been shown in empirical studies (e.g., Yeo et al, 2014). Therefore, more positive attitudes are considered to be the most influential factor for implementing successful inclusion (Avramidis and Norwich, 2002).…”
Section: Implicit and Explicit Attitudesmentioning
confidence: 99%
“…In addition, many teachers believe they are unqualified to educate students with disabilities (Vaz et al, 2015;Cassady, 2011;Mohamed et al, 2011;Avramidis and Kalyva, 2007;Greene, 2017). In other words, regular classroom teachers who work in traditional classrooms regard themselves as less competent in teaching students with disabilities than those who actually work in inclusive classrooms (Yeo et al, 2016). In China, if regular classroom teachers are minimally supported by their local educational authorities, they can master and use knowledge and techniques to teach students with disabilities in their classes (Deng and Harris, 2008).…”
Section: Teachers' Sense Of Self-efficacy In Teaching Students With Dmentioning
confidence: 99%
“…Regarding the relationship between teachers' perceived teaching efficacy and working in inclusive classrooms, some researchers found a positive relationship between teachers' perceived teaching efficacy and students' academic achievement (Ahsan et al, 2012;Goodwin, 2011;Mojavezi and Tamiz, 2012). Thus, teachers with high perceived teaching efficacy showed more effective teaching strategies (Chao et al, 2016) and their students showed higher levels of academic achievement (Woolfolk, 2007).…”
Section: Teachers' Teaching Efficacy Gender and Attitudes Toward Incmentioning
confidence: 99%
“…Les législations en faveur de l'intégration ou de l'inclusion scolaire ne peuvent à elles seules assurer la réussite de sa mise en oeuvre (Yeo, Chong, Neihart et Huan, 2016) et, conséquemment, la diminution des taux d'élèves scolarisés en classe spéciale. Reconnues comme un élément crucial de la réussite de la mise en oeuvre de l'école à visée inclusive, les attitudes des enseignantes ainsi que les facteurs qui les influencent ont été largement étudiés (Avramidis et Norwich, 2002 ;de Boer, Pijl et Minnaert, 2011).…”
Section: Introductionunclassified